Dams And Development- An Understanding Of Geologic, Socio-Economic And Environmental Impacts - Anjali Kumari; Prem Kumar; Harshulika; Arbin Kr. Thakur; Jaya Rai (Revista Electronica de Veterinaria, 2024)
Over 40 million people are said to have been relocated in India over the course of the previous 60 years due to the construction of 4,300 major dams. India currently has a serious water scarcity that affects domestic, industrial, and agricultural use. This is mostly the result of inadequate storage and ineffective water management. Recent patterns in decreased reservoir capacity seem to be a result of social and environmental opposition to developments as well as the necessity to restrict resettlement. In the light of advancement, there are numerous adverse social and environmental impacts being imposed on the habitants of the river basins. However, the regulatory authorities are enhancing the procedures to ensure that environmental and social repercussions are appropriately reviewed and controlled while being created to promote growth in order to ensure that the lessons of the past are learned and mistakes are avoided, or at least reduced.It is presumable that development at the national level affects project planning and practices through the creation of laws and policies, but it is individual projects where laws and policies actually take effect, where actual changes to higher social and environmental standards become evident, and possibly where these changes have cascading effects. Two policy areas will be examined for norm evolution and implementation: firstly, the use of environmental impact assessment along with the socio-economic effects on the lives of the people as a tool for planning and making decisions on dams; and secondly, the analysis of the resettlement policies such as the National Rehabilitation policy of 2007.